CENDAWAN MIKORIZA ARBUSKULA PADA RIZOSFER TANAMAN KAKAO ( Theobroma cacao L. ) DI TIPE KEMIRINGAN LAHAN YANG BERBEDA - Zahraeni Kumalawati; Andi Ridwan; Kafrawi Kafrawi (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2018)
The study aims to determine the potential diversity of arbuscular mycorrhizal fungi in cocoa plants in two different types of slope so that they can be used and developed as biological fertilizers to support cocoa productivity. The method used in this study was exploration method by randomly taking samples of mycorrhizal soil in two locations of community cocoa plantations with different types of land slopes in Polewali Mandar District, West Sulawesi. The wet filtering method was used to isolate mycorrhizal spores from soil samples to obtain mycorrhizal isolates as a source of inoculants. The mycorrhizal isolates obtained were identified based on morphological characters and their abundance in natural habitats was also calculated. The results of the study revealed that arbuscular mycorrhiza associated with cocoa plants in two types of land namely flat land and sloping land consisted of seven types of mycorrhizae belonging to 3 types of genera namely Glomeraceae, Gigasporaceae and Acaulosporaceae. Genus Glomeraceae showed higher dominance than genus Gigasporaceae, but genus Gigasporaceae can be found in both types of land. Arbuscular mycorrhiza whose spore count was limited to Sclerocytis sinousa, Scutellospora sp. and Acaulospora sp.